2011
DOI: 10.1177/1049732311430497
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Chronic Illness Self-Management

Abstract: Self-management is crucial for people living with chronic diseases, but the actual process of integrating self-management has not been explored in depth. In this article, we investigate the integration of self-management into the lives of people with chronic illness. In this longitudinal study, we used an interpretive description approach. Twenty-one individuals were interviewed regularly during the first 3 years after they were diagnosed with a chronic condition. We found self-management integration to be an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 29 publications
3
83
1
Order By: Relevance
“…Most of these strategies were not recommended by doctors but learned by participants either through research or experimentation. Participants appeared to fit into Audulv et al’s (2012) final stage of coping with their chronic illness as they had elicited information, weighed up the costs and benefits of coping strategies, created routines and reported being able to fit self-management into their daily lives. The patients in the study can also be characterised as proactive managers as they reported attempting to adopt healthy lifestyles in order to cope (Collins et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Most of these strategies were not recommended by doctors but learned by participants either through research or experimentation. Participants appeared to fit into Audulv et al’s (2012) final stage of coping with their chronic illness as they had elicited information, weighed up the costs and benefits of coping strategies, created routines and reported being able to fit self-management into their daily lives. The patients in the study can also be characterised as proactive managers as they reported attempting to adopt healthy lifestyles in order to cope (Collins et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Some SMI involved parents in the intervention or assessed family interaction or conflict. However, the notion that social context deserves attention when researching selfmanagement, has only recently gained more attention [14,17,19,[117][118][119][120].…”
Section: Page 13 Of 40mentioning
confidence: 99%
“…All people are influenced – positively and negatively—by their social networks, health-care providers and society as a whole. Each of these can provide both resources for and barriers to self-management [3]. Barriers and facilitators for self-management have been described in a large body of research.…”
Section: Introductionmentioning
confidence: 99%